Accident Prevention Behaviors among Older Adults Donkeaw, Maerim District, Chiangmai Province - ตินามาส พิกุล; จองแก ภัทรานิษฐ์; เส็งพานิช ทิพย์สุดา (Journal of Nurses Association of Thailand Northern Office, 2019)
The aim of this descriptive study were to describe accident prevention behaviors among older adults and to compare accident prevention behaviors among older adults by sex, age, underlying disease, income, and participation in senior’s citizen club. Participants were 327 older adults in Donkaew, Maerim district, Chiangmai province. The sample size was calculated by using Yamane’s formula. A quota sampling and convenient sampling technique were used to recruit older adults in each community. A research instrument included the Accidental Preventive Behaviors of the Elderlies questionnaire developed by Thitima Kumsuebsai. The reliability of questionnaire tested by Cronbach’s alpha coefficient was 0.84. Data was analyzed using descriptive statistics, Mann-Whitney test, and Kruskal-Wallis one-way analysis of variance. The results revealed that participants were female, aged 60-92 years old (mean age 71 years old). Majority of them graduated primary school. The mean score of accident prevention behaviors was at a moderate level. Regarding components of accident prevention behaviors, the highest mean score was insects bit prevention behavior ( = 2.49, S.D. = 0.38), while the lowest mean score was fall preventing behavior ( = 1.86, S.D. = 0.37). The differences between underlying diseases, participation in senior’s citizen club, and accident prevention behavior was statistically significant (p < .05). However, there was no statistically significant differences between gender, age, income, and accident prevention behaviors. Conclusion, the healthcare organization should encourage older adults to participate in senior’s citizen club and provide a fall prevention education for older adults in order to decrease all accidents and increase accident prevention behavior.